PENYUSUNAN SISTEM INFORMASI AKUNTANSI ORGANISASI NIRLABA UNTUK MENGHASILKAN LAPORAN KEUANGAN BERDASARKAN PSAK 45 (Studi Kasus pada Lingkar Sosial Malang) - Defina, Frida Kartika Putri (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research was conducted in one of the non-profit organization located in Malang, Lingkar Sosial which is focus to fight for the rights of the disabled, lepers, and also as one of the founding organizations of Forum Malang Inklusi. The purpose of this research is to know and evaluate how the accounting system that has been done by the Social Circle and provide recommendations for the resulting of accounting information system based on PSAK 45. This research is a descriptive qualitative research with case study method. Sources of the data derived from the primary data in the form of interviews and documentation, and the secondary data in the form of literature research results from the printed literature and internet media. The results of this study indicate that the accounting records has done in the Lingkar Sosial is still very simple and has not applied PSAK 45 due to the lack of knowledge of organizational board regarding accounting. However, the organizers of the organization have a desire to apply PSAK 45 because according to their standard report more conceptualized and structured. The researcher recommends an accounting information system based on the PSAK 45 which begins by changing the recording system from cash basis to accrual basis and single entry into double entry, identifying transactions, arranging charts of account and numbering for each account, making standard journal, preparing the general ledger format, and financial statements in accordance with PSAK 45. The financial statements according to PSAK 45 include activity reports, balance sheets, cash flow statements, and notes to the financial statements. After the preparation of accounting information system, in this study also provide examples of financial statements that have been reconstructed by using data of financial statements Lingkar Sosial year 2016.Keywords: non-profit organization, PSAK 45, accounting information system